Exploring the impact of the digital economy on green total factor productivity in China: A spatial econometric perspective - Sun, Xin; Jiang, Ke; Cui, Zhikun; Xu, Jilan; Zhao, Xin (Frontiers in Environmental Science, 2023)
The digital economy is considered a driving force of green economic development. However, only a few studies have examined the relationship between the digital economy and green total factor productivity (GTFP). According to the principal component method and super-efficient Slacks-based measure model, the digital economy level and GTFP were measured for China’s provinces based on panel data from 2013 to 2019. The spatial econometric model was then used to analyze the effects of the digital economy level on GTFP. Results showed that the overall level of GTFP maintained a steady growth trend, with an average yearly growth of 4.19%. Significant regional differences reflecting the development characteristics of eastern, central, and western regions were also observed. Most provinces showed either high or low values of both GTFP and digital economic development thereby revealing spatial heterogeneity for the different provinces and cities. The spatial Durbin model showed that the digital economy had a significant direct effect (0.1498) and spatial spillover effect (0.3438) on GTFP, the latter being greater than the former, with this conclusion supported by the robustness test. Technological innovation positively regulates the contribution of the region's digital economy to GTFP and negatively regulates the spatial spillover of the digital economy to GTFP in neighboring regions.